The Use of Trial-Based Functional Analysis in Public School Classrooms for Two Students With Developmental Disabilities. (July 2013) - Rispoli, Mandy J.; Davis, Heather S.; Goodwyn, Fara D.; Camargo, Síglia
Analogue functional analyses are a well-researched means of determining behavioral function in research and clinical contexts. However, conducting analogue functional analyses in school settings can be problematic and may lead to inconclusive results. The purpose of this study was to compare the results of a trial-based functional analysis with analogue functional analysis conducted within public school classrooms. Two individuals with developmental disabilities participated. Trial-based functional analyses produced clear behavioral functions for both participants, whereas analogue functional analysis results were inconclusive. Implications for practice and future research are presented.